2004
DOI: 10.1038/sj.bjp.0705915
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical characterisation of 111In‐DTPA‐trastuzumab

Abstract: In using DTPA as a chelator. In-DTPAtrastuzumab (labelling yield 92.372.3%, radiochemical purity 97.071.5%) is stable in PBS when stored at 41C for more than 14 days. The immunoreactive fraction determined by cell-binding assays, using the HER2-overexpressing human ovarian SK-OV-3 tumour cell line, was 0.8770.06. Biodistribution and tumour targeting were studied in HER2 receptor-positive and -negative tumour-bearing athymic mice. The HER2-positive tumour showed (9.7771.14% injected dose per gram (ID g À1 )) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
128
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(146 citation statements)
references
References 20 publications
16
128
2
Order By: Relevance
“…For example, radiolabeled trastuzumab and pertuzumab have been used for SPECT and PET of HER2 expression (13,14,16,31). However, these large proteins are characterized by slow tumor penetration and clearance from the circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, radiolabeled trastuzumab and pertuzumab have been used for SPECT and PET of HER2 expression (13,14,16,31). However, these large proteins are characterized by slow tumor penetration and clearance from the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been used for PET and SPECT of HER2 expression, including radiolabeled antibodies trastuzumab and pertuzumab (HER2 dimerization inhibitor) and radiolabeled trastuzumab fragments (13)(14)(15)(16). These radiotracers were able to visualize HER2 expression, but their large size resulted in slow tumor accumulation and slow clearance from the circulation.…”
mentioning
confidence: 99%
“…Using SPECT, we have shown HER2/neu-specific uptake of this radiopharmaceutical in xenograft-bearing animals (14) and HER2/neu-positive metastatic breast cancer patients (15). 111 In-diethylaminetriaminepentaacetic acid (DTPA)-trastuzumab scintigraphy revealed new tumor lesions in 13 of 15 patients and was therefore considered to be of potential value for clinical staging (15).…”
mentioning
confidence: 99%
“…The SK-OV-3 tumor showed substantial uptake of the labeled antibody after 5 h. The difference in uptake between SK-OV-3 and GLC4 tumors was even more pronounced 3 d after injection. At that time, the SK-OV-3 tumor was clearly visualized by radioimmunoscintigraphy (Lub-de Hooge et al, 2004). Research has also demonstrated that fluorescent dye-labeled trastuzumab enabled differentiation between breast cancer cells expressing high and low levels of HER2.…”
Section: Wwwintechopencom Targeting Egfr and Her2 For Molecular Imamentioning
confidence: 87%